Amyloid‐like Nanofibrillation of Metal‐Organic Complex Arrays Ruled by Their Precisely Designed Metal Sequences. Issue 6 (21st February 2020) - Rajmohan, Rajamani; Vrla, Geoffrey; Ueki, Hisanori; Sajna, Kappamveettil; Takei, Toshiaki; Ohtsu, Hiroyoshi; Kawano, Masaki; Vairaprakash, Pothiappan; Tashiro, Kentaro
Abstract: Self‐assembly of a series of dimetallic sequences constructed on a backbone with two successive tyrosine moieties (Fmoc‐M 1 ‐M 2 ‐CO2 H ) revealed that the resultant morphology is clearly dependent on the metal sequence, where Re‐containing sequences such as homometallic Fmoc‐Re‐Re‐CO2 H specifically afforded amyloid‐like nanofibers. These findings further allowed to achieve the fibrillation of a longer metal sequence containing three different metals (Fmoc‐Rh‐Pt‐Re‐Re‐CO2 H ). Cyclic voltammetry of the fibrillated Fmoc‐Re‐Re‐CO2 H demonstrated that the redox activity of the metal complexes in the sequence is preserved in the nanofibrous forms. Abstract : A series of multimetallic sequences constructed on a peptide backbone exhibited sequence‐dependent self‐assembly, where the di‐rhenium‐containing sequences showed a strong preference to form amyloid‐like nanofibers.